Mengenal Motivasi Belajar Dan Karakteristik Pribadi Siswa Dalam Meningkatkan Prestasi Belajar PAI - Asmawi HM (Pena Islam Jurnal Pendidikan Agama Islam, 2019)
Learning motivation is a very important learning need that cannot be separated from learning activities in order to achieve a goal. There is learning motivation that comes from yourself which is usually called intrinsic motivation, there are also those that come from outside oneself where emergence is needed from outside stimulation commonly called extrinsic motivation. With the existence of diligent effort and especially based on the existence of motivation, then someone who learns it will be able to give birth to achievements. Student Achievement is a result achieved or obtained by students from a learning process in achieving learning goals. Student achievement is a picture of students' ability to understand the content of a lesson which is usually symbolized by a score or value.